Fabrication of a Compact High-field Magnet by Coated Conductor Stacks. (September 2019) - Hashimoto, T; Pyon, S; Iijima, Y; Sugiura, S; Uji, S; Terashima, T; Tamegai, T
Abstract: A bulk magnet was fabricated by stacking coated conductors with enhanced J c by introducing nanorods. The fabricated CC stack consists of 100 pieces of CCs, and it was magnetized by field-cooling method in an applied field of 14.5 T down to 4.2 K. By reducing the magnetic field down to zero at a ramp of rate 1 T/min, we have succeeded in trapping 12.6 T at the center of the CC stack. We also confirmed that the CC stack can sustain the high trapped field for more than 20 min, which demonstrates the practical usefulness of such a staked CC magnet.